Community empowerment for elementary school children through handicrafts in developing local wisdom (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Community empowerment is one of the strategies in development. In the concept of development, human resources become important in an effort to increase the independence and internal strength of existing material and non-material resources. The concept of empowerment includes one's own strength, independence, self-choice, sovereignty of life in accordance with the values ​​adopted by a person or society, the capacity to fight for rights, independence, self-decision making, being free, awakening, and capabilities, which are basically embedded in values ​​and systems local beliefs. Community empowerment towards the village of tourism based on local wisdom (culture, agriculture, forestry, marine cultivation, and creative industries) is important to develop employment opportunities and try and increase community income. Crafts have great potential to be empowered.